New trends in quartz resonators developments and applications - BESSON, R. J. (Archives of Acoustics, 1991)
Piezoelectric quartz crystal oscillators are present in almost any frequency control equipment. Under those conditions important efforts have been devoted to quartz resonators and oscillators everywhere in the world. Also demanding and important has been the development of new quartz piezoelectric sensors. Then, quartz crystal resonator is the "heart" of frequency standards and sensor equipments as well. In this paper, quartz resonators are presented trying to provide important concepts for new developments and applications in the field. A short historical review providing general ideas is first presented. Then, since recent progress in resonator understanding and design have lead to overcome most previous limitations, the last important advances are pointed out and discussed. Basically, late improvements are largely due either to better theoretical understanding or to improvements of boundary conditions. Both are presented. Consequences are doubly rotated crystals, use of a crystal on two or three frequencies. Boundary conditions at the limits of the vibrating body have to be paid a great deal of attention. This leads to some new designs which include "unelectroded" crystals and "quartz monolithic mount" of resonators. Recent improvements in low aging, low external pressure variation sensitivity, fast warm-up are discussed in relation with different designs. Improvements of commercially available units are also presented according to several domains of application ranging from watch industry to high precision measurements. In conclusion, some new developments and applications are pionted out.